The Effect of Credit Risk Management on Financial Performance in the Banking Industry Listed on the Indonesia Stock Exchange - Amelinda Fairuz Azura; Pramesti Baskoro Dewi; Indri Ilma Yuannitha; Henny Setyo Lestari; Farah Margaretha (Journal of Social Research, 2023)
This study aims to empirically test credit risk management on financial performance measured by return on assets and return on equity at commercial banks listed on the Indonesian stock exchange in 2020-2022. The data was collected from 44 banks and examined by applying standard descriptive statistics and the random effect model for hypothesis testing. It is concluded from the regression outcomes that only loan to deposit ratio which has not a significant impact to return on asset but only loan to deposit ratio, risk asset ratio, and size are have a significant impact to return on equity. Based on these findings, it is suggested that bank companies must watch carefully the loans’ performance and analyze thoroughly the clients’ credit history an ability to pay back their debts prior to any approval of loan applications. The researchers recommend that future studies on credit risk management influence on banks’ financial performance should consider more independent variables and longer periods of study such as twenty or thirty years to have more accuracy and generalized results.